A Five-Year-Old Boy with Marked Hypergastrinemia Associated with H. pylori Infection - Asako Nakata; Hitoshi Tajiri; Yuri Etani; Sadami Kimura; Tomoko Takano (Case Reports in Gastroenterology, 2010)
A 5-year-old boy was referred to our department for persistent epigastric discomfort. Serum gastrin level was 635 pg/ml with a pepsinogen (PG) I level of 102.7 ng/ml and a PG I/II ratio of 23.2, indicating a hyperacidic state. Upper gastrointestinal endoscopy showed normal gastric mucosal folds and no abnormalities including no gastric mucosal atrophy. To investigate the cause of hypergastrinemia, a Ca injection test was performed and the patient showed no definitive response to a large load of Ca. Contrast-enhanced dynamic CT revealed no space-occupying lesions. The results from these two studies were not consistent with the presence of gastrinoma. A urea breath test showed 2.8‰, and a test for the fecal H. pylori antigen was positive. Since H. pylori infection was considered to be a possible cause of hypergastrinemia, eradication therapy was introduced. The therapy was shown to be successful by using a repeated urea breath test that showed a normalization to 0.6‰. 7 months after the therapy blood examination showed a gastrin level of 191 pg/ml, a PG I level of 36.7 ng/ml, and a PG I/II ratio of 7.3. An immunostaining study of the gastric mucosa suggested that a decrease in somatostatin secretion due to a reduction in D cell population might have induced hypergastrinemia in this case. In children with H. pylori infection showing marked hypergastrinemia, immunohistochemical examination and therapeutic diagnosis by eradication may be helpful in the differential diagnosis of gastrinoma.